Unraveling the role of the gut microbiome in pregnancy disorders: insights and implications - Xie, Yupei; Chen, Qian; Shan, Dan; Pan, Xiongfei; Hu, Yayi (Frontiers in Cellular and Infection Microbiology, 2025)
The gut microbiota is the collective term for the microorganisms that reside in the human gut. In recent years, advances in sequencing technology and bioinformatics gradually revealed the role of gut microbiota in human health. Dramatic changes in the gut microbiota occur during pregnancy due to hormonal and dietary changes, and these changes have been associated with certain gestational diseases such as preeclampsia (PE) and gestational diabetes mellitus (GDM). Modulation of gut microbiota has also been proposed as a potential treatment for these gestational diseases. The present article aims to review current reports on the association between gut microbiota and gestational diseases, explore possible mechanisms, and discuss the potential of probiotics in gestational diseases. Uncovering the link between gut microbiota and gestational diseases could lead to a new therapeutic approach.